Philosophy of Science as the Foundation for the Development of Islamic Da'wah - Nurhalifa, A.; Ramadhan, Muhammad Alif; Ilham, Muh.; Siola, Muh. Natsir (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The rapid development of science and technology necessitates a reflective foundation to ensure that their application remains aligned with humanistic and religious values, particularly in the practice of Islamic da‘wah. In this context, the philosophy of science plays a strategic role as a critical, reflective, and systematic framework for examining and developing da‘wah. This study aims to conceptually analyze the definition of the philosophy of da‘wah, the intellectual foundations underlying its emergence, the philosophical principles that support it, and the significance of philosophy in the development of Islamic da‘wah. This research employs a qualitative approach through library research, involving a critical analysis of relevant literature in the fields of philosophy of science and Islamic da‘wah. The findings indicate that the philosophy of da‘wah originates from the Qur’anic encouragement to employ reason, dialogue, and rational reflection, as well as from the scholarly need to position da‘wah as a scientific discipline with clear ontological, epistemological, and axiological foundations. The philosophy of da‘wah plays a vital role in strengthening the rational, methodological, and ethical dimensions of da‘wah, while also enhancing the capacity of preachers (da‘i) to respond to contemporary social challenges. Thus, the integration of the philosophy of science into Islamic da‘wah not only reinforces its theoretical and methodological aspects but also renders da‘wah more humanistic, contextual, adaptive, and oriented toward the welfare of society.